Artrodesis posterior C1-C2 mínimamente invasiva: NOTA TÉCNICA - Negri, Pablo; Vega, María Belén; Ernst, Nicolás; Gardella, Javier; Orellana, Marcelo (Revista Argentina de Neurocirugía, 2022)
INTRODUCTION: Nowadays, minimally invasive spinal surgery techniques are increasing in frequency. These new techniques aim to reduce pain and postoperative complications by avoiding muscle dissection compared to conventional surgeries. OBJECTIVE: To describe a new minimally invasive technique regarding posterior atlantoaxial fusion which was utilized in six patients with odontoid fracture. MATERIALS AND METHODS: Posterior C1-C2 fusion via minimally invasive technique was performed in six patients: three with a diagnosis of atlanto-axial instability secondary to type II odontoid process fracture, with listhesis fragment, two with C1-C2 instability associated to rheumatoid arthritis and one with C1-C2 instability associated to spondylodiscitis. with a type II odontoid fracture and secondary atlantoaxial instability. This technique is explained step by step, with details, which include skin incision, instrumentation through minimal access by tubular expandable retractors, the exposition of the lateral mass of C1, inferior articular process and pars interarticulares of C2, subperiosteal dissection of articular facets, and fixation of the C1 lateral mass and the C2 pedicle with polyaxial screws and rod, with the technique previously described by Harms and Melcher . RESULTS: This technique provides adequate anatomical exposure and allows for correct insertion of the screws, provides solid C1-C2 fixation, maintains pre-operative neurological status, and supports the avoidance of iatrogenic injuries. CONCLUSIONS: Minimally invasive surgery for posterior atlantoaxial fixation is a safe, feasible, and effective alternative with several potential advantages in selected cases. To show the real benefit of this approach, more extensive and comparative works between the minimally invasive and the conventional techniques are required.